2009
DOI: 10.1002/cpp.612
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graduate clinicians' personal therapy on therapeutic alliance

Abstract: This study investigates the effects of clinician personal therapy on therapeutic alliance early in treatment. Therapists who had received personal therapy assessed 30 outpatients, and therapists who had not undergone personal therapy assessed 30 outpatients. These groups of patients were matched on key demographic, diagnostic and psychiatric severity data. Results demonstrated no significant group differences on patient-rated alliance. Significant differences were observed for the therapist-rated alliance vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
1
23
3
1
Order By: Relevance
“…As with research regarding negative CT and client-clinician rapport, current research has found a link between training and treatment outcome (Bergin & Garfield, 1994; Gold & Hilsenroth, 2009; Harrison & Westwood, 2009; Minami et al, 2008). These findings are very important, as they allow us to understand a factor in how clinicians might mitigate experiences of negative CT. Gelso and Hayes (2002), in particular, found that the training used in supervision is a key factor in managing CT.…”
Section: Literature Reviewmentioning
confidence: 94%
“…As with research regarding negative CT and client-clinician rapport, current research has found a link between training and treatment outcome (Bergin & Garfield, 1994; Gold & Hilsenroth, 2009; Harrison & Westwood, 2009; Minami et al, 2008). These findings are very important, as they allow us to understand a factor in how clinicians might mitigate experiences of negative CT. Gelso and Hayes (2002), in particular, found that the training used in supervision is a key factor in managing CT.…”
Section: Literature Reviewmentioning
confidence: 94%
“…We based this hypothesis on the finding that clinicians with personal therapy had higher therapist-rated alliances with their patients than clinicians with no personal therapy (Gold & Hilsenroth, 2009). This hypothesis was not supported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gold and Hilsenroth (2009) examined the impact of graduate therapists' personal therapy on the therapeutic alliance early in treatment. In each of the two groups of trainees, with and without personal therapy, 30 outpatients were treated with psychodynamic therapy, once or twice per week.…”
mentioning
confidence: 99%
“…Although personal counseling has been endorsed (Hill, 2005;Kirsch, 2005;Laireiter & Willutzki, 2005;Lebow, 2005;Leech, 2007) and supports the personal and professional development of counselors, few counselors use personal counseling (Gold, 2010;Rake & Paley, 2009;Unkauf, 2010). Therefore the engagement in personal counseling needs to be examined.…”
Section: Most Of Jennings Andmentioning
confidence: 99%
“…When impairment is caused as a result of counseling practice, counselor trainees are often able to mitigate the negative effects of processing traumatic and upsetting client events through peer supervision (Dutton & Rubinstein, 1995), through professional supervision (Fernando & Hulse-Killacky, 2005), and other supports (Gold & Hilsenroth, 2009). However, sometimes these supports are not enough and so personal counseling may be helpful.…”
Section: Personal Counseling For Impaired Studentsmentioning
confidence: 99%